Heir of fire - Maas, Sarah J (New York, NY Bloomsbury, 2015)
Royal assassin Celaena must travel to a new land to confront a truth about her heritage, while brutal and monstrous forces are gathering on the horizon, intent on enslaving her world
Sequel to: Crown of midnight
1
Keywords: Assassins -- Juvenile fiction; Identity (Philosophical concept) -- Juvenile fiction; Young adult fiction